Do public works programs crowd-out pro-environmental behavior? Empirical evidence from food-for-work programs in Ethiopia - Goytom Abraha Kahsay; Workineh Asmare Kassie; Abebe Damte Beyene; Lars Gårn Hansen (University of Copenhagen, Department of Food and Resource Economics (IFRO), 2017)
The Ethiopian food for work program typically induces forest conservation work. While economic outcomes have been studied before, little is known about the program's environmental impact. We run a choice experiment among Ethiopian farmers eliciting preferences in a hypothetical afforestation program that mimics the Ethiopian food-for-work program. We find that introducing food incentives decreases willingness to participate in the program and participation rate increases with an increase in the proportion of individuals selected for food incentive. We also find that the crowding-out effect is stronger when food incentive recipients are selected based on income compared to lottery-based selection. Our data points to pro-social signaling as the most likely channel for the crowding-out effect. These results suggest that (1) food-for-work programs could have unintended negative environmental effects and (2) directions for design reform that could mitigate this.
Keywords: D03; D64; D82; Q57; 330; Crowding-out; Food-for-work program; Pro-environmental behavior; Selection; Pro-social signaling